2003
DOI: 10.2165/00019053-200321030-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Quality-of-Life Estimates for Stroke

Abstract: We found no systematic difference in stroke QOL weights depending on elicitation method or respondents. However, quality of life is sensitive to the bounds of the scale. Because the pooled QOL estimates reported here are based on a comprehensive review of the QOL literature for stroke, they should be of great use to researchers performing cost-utility analyses of interventions designed to prevent or treat stroke, or where stroke is a possible side effect of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(115 citation statements)
references
References 34 publications
5
105
2
3
Order By: Relevance
“…This is the median value reported in a systematic review of utility estimates after stroke. 115,116 This included 67 studies using a range of preference elicitation methods, carried out in patients, members of the general public and clinicians.…”
Section: Cost-effectiveness Of Dual-chamber Pacingmentioning
confidence: 99%
“…This is the median value reported in a systematic review of utility estimates after stroke. 115,116 This included 67 studies using a range of preference elicitation methods, carried out in patients, members of the general public and clinicians.…”
Section: Cost-effectiveness Of Dual-chamber Pacingmentioning
confidence: 99%
“…The other study was a meta-analysis of quality of life estimates for stroke. 245 Studies were identified by searching through NHS EED and MEDLINE, as well as examining bibliographies of review articles and citation searching. In total, 20 articles were found, reporting 53 quality of life estimates.…”
mentioning
confidence: 99%
“…Major and minor stroke events were assigned utility values of 0.39 and 0.77, respectively, based on time tradeoff estimates from a stroke population; 44% of strokes were assumed to be major (29). Other sources for stroke utilities were used in sensitivity analyses (28,30). Undergoing a CEA procedure was assigned a utility value of 0.77, on the basis of the EQ-5D instrument used in a revascularization clinical trial, for 2 weeks (34).…”
Section: Resultsmentioning
confidence: 99%